Glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device, a magnetic recording medium substrate, a magnetic recording medium, a glass spacer for a magnetic recording / reproducing device, and a magnetic recording / reproducing device
A glass substrate with tailored chemical composition addresses the heat resistance and productivity issues of aluminum alloy substrates, ensuring stable high-temperature processing and improved manufacturing efficiency for magnetic recording media.
Patent Information
- Application Number
- JP2023134923
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-13
- Filing Date
- 2023-08-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Existing magnetic recording media substrates made of aluminum alloys are prone to deformation due to insufficient heat resistance, necessitating the development of a glass substrate with high heat resistance and improved productivity for high-temperature processing.
A glass composition with specific ratios of Li2O, Na2O, K2O, B2O3, ZnO, SiO2, Al2O3, MgO, and CaO, tailored to achieve a glass transition temperature of 740°C or higher, ensuring excellent heat resistance and productivity, suitable for magnetic recording media substrates and spacers.
The glass substrate exhibits high heat resistance, enabling stable high-temperature processing and maintaining substrate flatness, while also enhancing productivity through improved melting properties and prolonged polishing pad life.
Smart Images

Figure 0007621437000001 
Figure 0007621437000002 
Figure 0007621437000003
Abstract
Description
[Technical field]
[0001] The present invention relates to glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device, a magnetic recording medium substrate, a magnetic recording medium, a glass spacer for a magnetic recording / reproducing device, and a magnetic recording / reproducing device. [Background technology]
[0002] Aluminum alloy substrates have been used as substrates for magnetic recording media such as hard disks (magnetic recording media substrates). However, it has been pointed out that aluminum alloy substrates are prone to deformation, etc. For this reason, glass magnetic recording media substrates are now widely used.
[0003] Patent Document 1 discloses an alkali-free glass, and states that the glass described in this document can also be used as a glass substrate for a magnetic disk (see paragraph 0014 of Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-224150 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the process of forming a magnetic recording layer on a magnetic recording medium substrate, the film is usually formed at a high temperature, or a heat treatment is performed at a high temperature after the film is formed. Therefore, the glass for the magnetic recording medium substrate is required to have high heat resistance capable of withstanding the high-temperature treatment, specifically, to have a high glass transition temperature.
[0006] Furthermore, glass for magnetic recording medium substrates is also required to be easy to produce, that is, to have excellent productivity.
[0007] As described above, it is desirable for glass for magnetic recording medium substrates to have excellent heat resistance and productivity. However, as a result of the inventor's investigation, it became clear that although Patent Document 1 discloses glass with a high glass transition temperature, improvement is required in terms of productivity.
[0008] An object of one aspect of the present invention is to provide a glass for a magnetic recording medium substrate that is excellent in both heat resistance and productivity. [Means for solving the problem]
[0009] One aspect of the present invention is The total content of Li2O, Na2O, K2O, B2O3 and ZnO (Li2O+Na2O+K2O+B2O3+ZnO) is 0 mol% or more and 3 mol% or less, The molar ratio of the total content of Al2O3 and MgO to the total content of SiO2 and CaO [(Al2O3+MgO) / (SiO2+CaO)] is 0.30 or more and 0.6 or less; The total content of SiO2 and Al2O3 (SiO2 + Al2O3) is 64 mol% or more and 85 mol% or less, and The total content of SiO2, Al2O3, MgO and CaO (SiO2+Al2O3+MgO+CaO) is 87 mol% or more and 98 mol% or less, A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device (hereinafter also referred to as "glass A"). Regarding.
[0010] Another aspect of the present invention is The molar ratio of the total content of Al2O3 and MgO to the total content of SiO2 and CaO [(Al2O3+MgO) / (SiO2+CaO)] is 0.30 or more and 0.6 or less; The total content of SiO2 and Al2O3 (SiO2 + Al2O3) is 64 mol% or more and 85 mol% or less, The total content of SiO2, Al2O3, MgO and CaO (SiO2+Al2O3+MgO+CaO) is 87 mol% or more and 98 mol% or less, and Glass transition temperature is 740℃ or higher, A glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device (hereinafter also referred to as "glass B"). Regarding.
[0011] Glass A and glass B have the above glass composition and can have excellent heat resistance and excellent productivity. Excellent productivity, for example, in one embodiment, means excellent solubility. Also, excellent productivity, for example, in one embodiment, means that the same polishing pad can be used for a longer period of time in the polishing process that is usually performed to process into a magnetic recording medium substrate. Glass having excellent heat resistance and excellent productivity is suitable as a glass for a magnetic recording medium substrate, and is also suitable as a glass for a glass spacer for a magnetic recording and reproducing device. Effect of the Invention
[0012] According to one aspect of the present invention, it is possible to provide a glass for a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device, which has excellent heat resistance and productivity. According to another aspect, it is also possible to provide a magnetic recording medium substrate made of the above glass, and a magnetic recording medium including the substrate. According to yet another aspect, it is possible to provide a glass spacer for a magnetic recording device made of the above glass. According to yet another aspect, it is possible to provide a magnetic recording / reproducing device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [Glass] Glass A and glass B are glasses for magnetic recording medium substrates or glass spacers for magnetic recording / reproducing devices, and can be amorphous glasses. Unlike crystallized glass, amorphous glass is glass that does not substantially contain a crystalline phase and exhibits a glass transition phenomenon upon heating. The glass may be an amorphous oxide glass, which is a glass in which the main network-forming component is an oxide. The above glass will now be described in more detail.
[0014] Hereinafter, glass A and glass B will be described in more detail. Unless otherwise specified, the description of glass A can also be applied to glass B, and the description of glass B can also be applied to glass A.
[0015] In the present invention and this specification, the glass composition is expressed as a glass composition based on oxides. Here, "glass composition based on oxides" refers to a glass composition obtained by converting the glass raw materials into oxides that are present in the glass after being completely decomposed during melting. Furthermore, unless otherwise specified, the glass composition is expressed on a molar basis (mol %, molar ratio). The glass composition of the present invention and this specification can be determined by a method such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Quantitative analysis is performed for each element using ICP-AES. The analytical values are then converted into oxide notation. The analytical values obtained by ICP-AES may contain a measurement error of, for example, about ±5% of the analytical value. Therefore, the oxide notation values converted from the analytical values may also contain an error of about ±5%. In the present invention and this specification, the content of a component being 0% or not being contained or not being introduced means that the component is substantially not contained, and the content of the component is at or below the impurity level. At or below the impurity level means, for example, less than 0.01%.
[0016] <Glass A> (Glass composition) From the viewpoint of improving heat resistance, the total content of Li2O, Na2O, K2O, B2O3 and ZnO (Li2O+Na2O+K2O+B2O3+ZnO) is 3% or less, preferably 2.8 or less, more preferably 2.6 or less, even more preferably 2.4 or less, even more preferably 2.0 or less, even more preferably 1.5 or less, even more preferably 1.0 or less, even more preferably 0.8 or less, and even more preferably 0.5 or less. The total content of Li2O, Na2O, K2O, B2O3 and ZnO (Li2O+Na2O+K2O+B2O3+ZnO) is 0% or more, can be 0%, can be more than 0%, can be 0.1% or more, 0.2% or more, or 0.3% or more.
[0017] The molar ratio of the total content of Al2O3 and MgO to the total content of SiO2 and CaO [(Al2O3+MgO) / (SiO2+CaO)] is 0.30 or more, preferably 0.32 or more, more preferably 0.34 or more, even more preferably 0.36 or more, and even more preferably 0.38 or more, from the viewpoint of improving productivity, especially from the viewpoint of enabling the same polishing pad to be used for a longer period of time. Also, the molar ratio [(Al2O3+MgO) / (SiO2+CaO)] is 0.6 or less, preferably 0.60 or less, more preferably 0.58 or less, even more preferably 0.56 or less, even more preferably 0.54 or less, even more preferably 0.52 or less, and even more preferably 0.50 or less, from the viewpoint of improving glass stability.
[0018] The total content of SiO2 and Al2O3 (SiO2+Al2O3) is 85% or less, preferably 83% or less, from the viewpoint of improving productivity, particularly from the viewpoint of improving the meltability of glass. Also, from the viewpoint of enabling glass to exhibit a viscosity suitable for molding at a molding temperature suitable for molding glass with good productivity, the total content of SiO2 and Al2O3 (SiO2+Al2O3) is preferably 82% or less, more preferably 81% or less. Also, from the viewpoint of improving chemical durability, the total content of SiO2 and Al2O3 (SiO2+Al2O3) is 64% or more, preferably 66% or more, more preferably 68% or more, and even more preferably 70% or more.
[0019] The total content of SiO2, Al2O3, MgO and CaO (SiO2+Al2O3+MgO+CaO) is 87% or more from the viewpoint of improving heat resistance. The total content (SiO2+Al2O3+MgO+CaO) of 87% or more is also preferable from the viewpoint of improving glass stability and reducing the specific gravity of glass. From the above viewpoints, the total content (SiO2+Al2O3+MgO+CaO) is preferably 89% or more, more preferably 91% or more, and even more preferably 93% or more. Furthermore, from the viewpoint of improving glass stability, the total content (SiO2+Al2O3+MgO+CaO) is 98% or less, preferably 97% or less, and more preferably 96% or less.
[0020] SiO2 is a glass network forming component. From the viewpoint of further improving glass stability, the SiO2 content is preferably 55% or more, more preferably 57% or more, and even more preferably 59% or more. From the viewpoint of further improving productivity, particularly from the viewpoint of further improving glass meltability, the SiO2 content is preferably 66% or less, more preferably 64% or less, and even more preferably 63% or less.
[0021] B2O3 is also a glass network forming component. The B2O3 content can be 0% or more, can be 0%, or can be more than 0%. B2O3 is easily volatilized during melting and tends to destabilize the glass component ratio. In addition, excessive introduction tends to reduce chemical durability. From the above viewpoint, the B2O3 content can be, for example, 3% or less, preferably 2% or less, more preferably 1% or less, and even more preferably 0%.
[0022] From the viewpoint of further improving the heat resistance, the Al2O3 content is preferably 10% or more, more preferably 11% or more, and even more preferably 12% or more. From the viewpoint of further improving the glass stability, the Al2O3 content is preferably 18% or less, more preferably 17% or less, and even more preferably 16% or less.
[0023] The P2O5 content can be 0% or more, can be 0%, or can be more than 0%. From the viewpoint of further improving glass stability, the P2O5 content is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.3% or less.
[0024] From the viewpoint of improving the rigidity of the glass, for example, increasing the Young's modulus, the MgO content is preferably 8% or more, more preferably 9% or more, even more preferably 10% or more, and even more preferably 12% or more. From the viewpoint of further improving the stability of the glass, the MgO content is preferably 20% or less, more preferably 19% or less, and even more preferably 18% or less.
[0025] The CaO content can be 0% or more, can be 0%, or can be more than 0%. From the viewpoint of further improving glass stability, the CaO content is preferably more than 0%, more preferably 0.5% or more, even more preferably 1% or more, even more preferably 1.5% or more, and even more preferably 2% or more. In addition, from the viewpoint of further improving productivity, especially from the viewpoint of enabling the same polishing pad to be used for a longer period of time, the CaO content is preferably 7% or less, more preferably 6% or less, and even more preferably 5% or less.
[0026] From the viewpoint of further improving the glass stability, the total content of Al2O3, MgO and CaO (Al2O3+MgO+CaO) is preferably 38% or less, more preferably 35% or less, and even more preferably 34% or less. From the viewpoint of improving the rigidity of the glass, for example, the Young's modulus, the total content (Al2O3+MgO+CaO) is preferably 26% or more, more preferably 28% or more, and even more preferably 30% or more.
[0027] The BaO content may be 0% or more, may be 0%, may be more than 0%, may be 0.5% or more, or may be 1% or more. From the viewpoint of decreasing the specific gravity of the glass, the BaO content is preferably 3% or less, more preferably 2.5% or less, and further preferably 2% or less.
[0028] The SrO content may be 0% or more, or may be 0% or more, and from the viewpoint of further improving the glass stability, it is preferably more than 0%, more preferably 0.5% or more, and even more preferably 1% or more. From the viewpoint of reducing the specific gravity of the glass, the SrO content is preferably 5% or less, more preferably 4.5% or less, even more preferably 4% or less, even more preferably 3.5% or less, and even more preferably 3% or less.
[0029] The molar ratio of the CaO content to the total content of MgO, CaO, SrO and BaO [CaO / (MgO+CaO+SrO+BaO)] can be 0 or can be greater than 0. From the viewpoint of further improving the glass stability, the molar ratio [CaO / (MgO+CaO+SrO+BaO)] is preferably greater than 0. From the viewpoint of further improving productivity, and in particular from the viewpoint of enabling the same polishing pad to be used for an even longer period of time, the molar ratio [CaO / (MgO+CaO+SrO+BaO)] is preferably 0.36 or less, more preferably 0.34 or less, even more preferably 0.32 or less, still more preferably 0.30 or less, and even more preferably 0.28 or less.
[0030] The ZnO content may be 0% or more, may be 0%, may be more than 0%, may be 0.5% or more, or may be 1% or more. From the viewpoint of further improving the glass stability, the ZnO content is preferably 2% or less, more preferably 1.5% or less, and even more preferably 1% or less.
[0031] The total content of ZnO and BaO (ZnO+BaO) may be 0%, may be more than 0%, or may be 0.5% or more, or may be 1% or more. From the viewpoint of decreasing the specific gravity of the glass, the total content (ZnO+BaO) is preferably 2.5% or less, more preferably 2.3% or less, and further preferably 2.0% or less.
[0032] The ZrO2 content may be 0% or more, may be 0%, may be more than 0%, may be 0.5% or more, or may be 1% or more. From the viewpoint of further improving glass stability, the ZrO2 content is preferably 4% or less, more preferably 3.5% or less, even more preferably 3% or less, even more preferably 2.5% or less, and even more preferably 2% or less.
[0033] The Li2O content may be 0% or more, may be 0%, or may be more than 0%. From the viewpoint of further improving heat resistance, the Li2O content is preferably 3% or less, more preferably 2% or less, even more preferably 1% or less, even more preferably 0.5% or less, and even more preferably 0.3% or less.
[0034] The Na2O content can be 0% or more, can be 0%, or can be more than 0%. Also, the Na2O content can be, for example, 3% or less, 2.5% or less, or 2% or less.
[0035] The K2O content can be 0% or more, can be 0%, or can be more than 0%. Also, the K2O content can be, for example, 3% or less, 2.5% or less, or 2% or less.
[0036] From the viewpoint of further improving the heat resistance, the molar ratio of the total content of MgO, CaO, Li2O, Na2O and K2O to the content of Al2O3 [(MgO+CaO+Li2O+Na2O+K2O) / Al2O3] is preferably 2 or less, more preferably 1.7 or less, and even more preferably 1.5 or less. From the viewpoint of further improving the productivity, especially the meltability of the glass, the molar ratio [(MgO+CaO+Li2O+Na2O+K2O) / Al2O3] is preferably 0.8 or more, more preferably 1.0 or more, and even more preferably 1.2 or more.
[0037] The TiO2 content may be 0% or more, may be 0%, may be more than 0%, may be 0.5% or more, or may be 1% or more. From the viewpoint of further improving glass stability, the TiO2 content is preferably 5% or less, more preferably 4.5% or less, even more preferably 4% or less, even more preferably 3.5% or less, even more preferably 3% or less, even more preferably 2.5% or less, and even more preferably 2% or less.
[0038] The total content of TiO2 and ZrO2 (TiO2+ZrO2) may be 0% or more than 0%, and from the viewpoint of improving the rigidity of the glass, for example, from the viewpoint of increasing the Young's modulus, it is preferably more than 0%, more preferably 0.5% or more, even more preferably 1% or more, and even more preferably 2% or more. From the viewpoint of reducing the specific gravity of the glass, the total content (TiO2+ZrO2) is preferably 6% or less, more preferably 5% or less, even more preferably 4% or less, and even more preferably 3% or less.
[0039] The molar ratio of TiO2 content to the total content of Al2O3, ZrO2 and SrO [TiO2 / (Al2O3+ZrO2+SrO)] is preferably 0.15 or less, more preferably 0.1 or less, even more preferably 0.5 or less, even more preferably 0.1 or less, and even more preferably 0.08 or less, from the viewpoint of improving glass stability. The molar ratio [TiO2 / (Al2O3+ZrO2+SrO)] may be 0 or more, 0 or more, and from the viewpoint of further improving productivity, especially further improving the meltability of glass, it is preferably more than 0, more preferably 0.01 or more, and even more preferably 0.03 or more.
[0040] The total content of B2O3, SrO, TiO2 and ZrO2 (B2O3+SrO+TiO2+ZrO2) may be 0%, may be more than 0%, may be 0.5% or more, or may be 1% or more. From the viewpoint of further improving the glass stability, the total content (B2O3+SrO+TiO2+ZrO2) is preferably 7% or less, more preferably 6.5% or less, even more preferably 6% or less, and even more preferably 5.5% or less.
[0041] From the viewpoint of reducing the specific gravity of the glass, the PbO content is preferably 0.5% or less, more preferably 0.3% or less, and even more preferably 0.1% or less. The PbO content can be 0% or more, and can also be 0%. Since PbO is a substance that has a negative effect on the environment, it is preferable to reduce its content or avoid its introduction (i.e., to make the content 0%). Cd and As are also substances that have a negative effect on the environment, so it is preferable to avoid the introduction of these as well.
[0042] The above glass may contain one or more elements selected from the group consisting of SnO2, CeO2 and Sb2O3 from the viewpoint of obtaining a clarification effect. SnO2 has the function of promoting fining when the melting temperature of the glass is relatively high (temperature range of about 1400 to 1600°C). The SnO2 content may be 0% or more, 0%, or more than 0%. In a situation where the use of fining agents that have an adverse effect on the environment, such as Sb2O3 and arsenous acid, is restricted, in one embodiment, it is preferable to introduce SnO2 into glass A in order to remove bubbles in glass with a high melting temperature. From the viewpoint of obtaining a fining effect, the content of SnO2 is preferably 0.01% or more, more preferably 0.05% or more, even more preferably 0.10% or more, even more preferably 0.15% or more, and even more preferably 0.20% or more. In addition, from the viewpoint of reducing the specific gravity of the glass, the content of SnO2 is preferably 2% or less, more preferably 1.5% or less, even more preferably 1% or less, even more preferably 0.8% or less, and even more preferably 0.5% or less.
[0043] CeO2 is also a component that exhibits a fining effect on glass. The CeO2 content may be 0% or more, 0%, or more than 0%. CeO2 has the function of taking in oxygen and fixing it as a glass component when the melting temperature of the glass is relatively low (temperature range of about 1200 to 1400°C), so in one embodiment, it is preferable to introduce CeO2 into the above glass as a fining agent. From the viewpoint of obtaining a fining effect, the content of CeO2 is preferably 0.01% or more, more preferably 0.05% or more, even more preferably 0.08% or more, and even more preferably 0.10% or more. In addition, from the viewpoint of reducing the specific gravity of the glass, the content of CeO2 is preferably 2% or less, more preferably 1.5% or less, even more preferably 1% or less, even more preferably 0.8% or less, even more preferably 0.5% or less, and even more preferably 0.3% or less. The coexistence of SnO2 and CeO2 provides a fining effect over a wide temperature range, so in one embodiment, the glass preferably contains both SnO2 and CeO2.
[0044] From the viewpoint of reducing the environmental load, it is desirable to refrain from using Sb2O3. The Sb2O3 content is preferably in the range of 0 to 0.5%. The Sb2O3 content is more preferably 0.3% or less, even more preferably 0.1% or less, even more preferably 0.05% or less, and even more preferably 0.02% or less, and it is particularly preferable that no Sb2O3 is contained (the content is 0%).
[0045] The Fe2O3 content may be 0% or more, 0%, or more than 0%. It is preferable to include Fe2O3 in glass from the viewpoint of improving the heat absorption efficiency during heating. For example, a magnetic recording medium substrate made of glass with high heat absorption efficiency during heating can contribute to improving the heating efficiency during and / or after the deposition of a magnetic layer in the manufacturing process of a magnetic recording medium, and is therefore preferable from the viewpoint of improving productivity. From the viewpoint of further improving glass stability, the Fe2O3 content is preferably 1% or less, more preferably 0.5% or less, even more preferably 0.1% or less, and even more preferably 0.05% or less. The Fe2O3 content is expressed as an external percentage. That is, when the total content of components other than Fe2O3 contained in the glass (the total content of the glass components and additives when additives are included in addition to the glass components) is taken as 100%, the Fe2O3 content is expressed as the molar percentage of the Fe2O3 content relative to 100%.
[0046] (Glass properties) Glass transition temperature As described above, the magnetic recording medium substrate is usually subjected to high temperature treatment in the process of forming a magnetic recording layer on the substrate. For example, in order to form a magnetic recording layer containing a magnetic material with high magnetic anisotropic energy, which has been developed in recent years for high density recording of magnetic recording media, a film is usually formed at a high temperature, or a heat treatment is performed at a high temperature after film formation. If the magnetic recording medium substrate does not have heat resistance capable of withstanding such high temperature treatment, the substrate will be exposed to high temperatures in the high temperature treatment and the flatness of the substrate will be damaged. In contrast, glass A can exhibit high heat resistance by having the above glass composition. Regarding the glass transition temperature (hereinafter also referred to as "Tg"), which is an index of heat resistance, the Tg of glass A is preferably 740°C or higher, more preferably 750°C or higher, even more preferably 760°C or higher, and even more preferably 770°C or higher. In addition, the Tg of glass A can be, for example, 850°C or lower, 830°C or lower, or 810°C or lower, but is not limited to the above exemplified values, since a higher Tg is more preferable from the viewpoint of heat resistance.
[0047] Young's Modulus As magnetic recording media become thinner and recording densities become higher, there are increasing demands for further reduction in warping and deflection of magnetic recording media during rotation of a spindle motor and for practical strength of magnetic recording media. In order to meet these demands, it is desirable for the glass for magnetic recording medium substrates to have high rigidity, specifically, a high Young's modulus. In this regard, the Young's modulus of glass A is preferably 86 GPa or more. According to a glass for magnetic recording medium substrates having high rigidity, which shows a Young's modulus of 86 GPa or more, it is possible to suppress the deformation of the substrate during rotation of a spindle motor, and therefore it is possible to suppress the warping and deflection of the magnetic recording medium caused by the deformation of the substrate. The Young's modulus of glass A is more preferably 88 GPa or more, more preferably 90 GPa or more, even more preferably 92 GPa or more, and even more preferably 94 GPa or more. The Young's modulus of glass A can be, for example, 120 GPa or less, 110 GPa or less, or 100 GPa or less, but is not limited to the above-mentioned values, since the higher the Young's modulus, the higher the rigidity and the more preferable it is.
[0048] specific gravity The specific gravity of glass A is preferably 2.8 or less. The specific gravity of glass A is more preferably 2.80 or less, even more preferably 2.78 or less, even more preferably 2.76 or less, even more preferably 2.74 or less, even more preferably 2.72 or less, and even more preferably 2.70 or less. The low specific gravity of the glass for magnetic recording medium substrate can reduce the weight of the magnetic recording medium substrate, and further reduce the weight of the magnetic recording medium, thereby enabling the reduction of power consumption of the magnetic recording and reproducing device (generally called HDD). The specific gravity of glass A can be, for example, 2.40 or more, but is not limited to the above exemplified values, since the lower the specific gravity, the more preferable it is.
[0049] Specific Elastic Modulus The specific elastic modulus is the Young's modulus of the glass divided by its density, where density is the specific gravity of the glass multiplied by the unit of g / cm 3 It may be considered as a value with a unit of "specific elasticity modulus". From the viewpoint of providing a substrate that is less likely to deform, the specific elasticity modulus of glass A is preferably 30 MNm / kg or more, more preferably 32 MNm / kg or more, even more preferably 33 MNm / kg or more, even more preferably 34 MNm / kg or more, and even more preferably 35 MNm / kg or more. The specific elasticity modulus can be, for example, 40 MNm / kg or less, but since the higher the specific elasticity modulus, the more preferable it is, it is not limited to the above exemplified values.
[0050] Thermal expansion coefficient HDDs incorporating magnetic recording media are usually structured so that the center part is held down by the spindle and clamp of a spindle motor to rotate the magnetic recording medium itself. Therefore, if there is a large difference in the thermal expansion coefficients of the magnetic recording medium substrate and the spindle material that constitutes the spindle part, there will be a mismatch between the thermal expansion and contraction of the spindle and the magnetic recording medium substrate in response to changes in the ambient temperature during use, resulting in deformation of the magnetic recording medium. If this phenomenon occurs, the head will not be able to read the written information, which will cause a decrease in the reliability of recording and playback. Therefore, it is desirable to prevent the difference between the thermal expansion coefficient of the glass for the magnetic recording medium substrate and that of the spindle material (such as stainless steel) from becoming too large. In general, the thermal expansion coefficient of the spindle material for HDDs is 70×10 -7 / °C or more, and the average linear expansion coefficient (thermal expansion coefficient) of the glass for magnetic recording medium substrates at 100 to 300°C is 30×10 -7 / °C or more, the difference in thermal expansion coefficient with the spindle material is small, which can contribute to improving the reliability of the magnetic recording medium. The average linear expansion coefficient (hereinafter also referred to as "α") of glass A at 100 to 300°C is 34×10 -7 / ℃ or more, and 35×10 -7 / °C or more, and more preferably 36×10 -7 / °C or more, and more preferably 37×10 -7 / °C or more, and more preferably 38×10 -7 / °C or more, and more preferably 39×10 -7 / °C or more. The average linear expansion coefficient (α) of glass A at 100 to 300°C is preferably 70×10 -7 / ℃ or less, and 68×10 -7 / °C or less, and more preferably 65×10 -7 / °C or less, more preferably 63×10 -7 / °C or less, and more preferably 60×10 -7 / °C or less, and more preferably 57×10 -7It is even more preferable that the temperature is 0.1 to 100° C. / ° C. or less.
[0051] Glass Stability Glass A can preferably exhibit high glass stability. Examples of methods for evaluating glass stability include a 1300°C, 1270°C, or 1250°C 16-hour retention test, which will be described in detail below. In one or more retention tests of the 1300°C 16-hour retention test, the 1270°C 16-hour retention test, and the 1250°C 16-hour retention test, the evaluation result is preferably A or B, and more preferably A. It can be said that the better the result in the retention test at a lower retention temperature, the higher the glass stability.
[0052] <Glass B> (Glass composition) In glass B, the molar ratio of the total content of Al2O3 and MgO to the total content of SiO2 and CaO [(Al2O3+MgO) / (SiO2+CaO)] is 0.30 or more and 0.6 or less. For details about the molar ratio [(Al2O3+MgO) / (SiO2+CaO)] of glass B, the above description of glass A can be referred to.
[0053] In glass B, the total content of SiO2 and Al2O3 (SiO2+Al2O3) is 64 mol % or more and 85 mol % or less. For details about the total content (SiO2+Al2O3) of glass B, the above description of glass A can be referred to.
[0054] In glass B, the total content of SiO2, Al2O3, MgO and CaO (SiO2+Al2O3+MgO+CaO) is 87 mol% or more and 98 mol% or less. For details of the total content (SiO2+Al2O3+MgO+CaO) of glass B, the above description of glass A can be referred to.
[0055] In glass B, the total content of Li2O, Na2O, K2O, B2O3, and ZnO (Li2O+Na2O+K2O+B2O3+ZnO) is preferably 0 mol % or more and 3 mol % or less. For details of the total content (Li2O+Na2O+K2O+B2O3+ZnO) in glass B, the above description of glass A can be referred to.
[0056] For other details of the glass composition of glass B, reference can be made to the above description of glass A.
[0057] (Glass properties) The glass transition temperature of glass B is greater than or equal to 740° C. For details of the glass transition temperature of glass B, reference can be made to the above description of glass A. For other details of the physical properties of the glasses, the above description of Glass A can be referred to.
[0058] Glass A and glass B can be produced by weighing, mixing, and thoroughly mixing glass raw materials such as oxides, carbonates, nitrates, sulfates, and hydroxides so as to obtain a desired glass composition, and then heating and melting the mixture in a melting vessel at, for example, a range of 1400 to 1600°C, clarifying, stirring, and forming a homogenized molten glass that has been sufficiently bubble-free. For example, it is preferable to heat and melt the glass raw materials in a melting tank at 1400 to 1550°C, and then raise the temperature of the obtained molten glass in a fining tank and hold it at 1450 to 1600°C, and then lower the temperature to 1200 to 1400°C to allow the glass to flow and be formed. Regarding the meltability of glass, it can be said that the less the raw materials remain unmelted when melted at a certain melting temperature, the better the meltability. Glass having excellent melting properties can be homogeneously melted at a lower temperature or in a shorter time, and is therefore preferred from the viewpoint of productivity.
[0059] [Magnetic recording medium substrate] A magnetic recording medium substrate according to one embodiment of the present invention (hereinafter also referred to as “magnetic recording medium substrate a”) is made of glass A. A magnetic recording medium substrate according to another embodiment of the present invention (hereinafter also referred to as “magnetic recording medium substrate b”) is made of Glass B.
[0060] The magnetic recording medium substrate can be manufactured by heating glass raw materials to prepare a glass melt, forming the glass melt into a plate shape by any of the press molding, down-draw, and float methods, and processing the obtained plate-shaped glass. For example, in the press molding method, the glass melt flowing out of a glass outflow pipe is cut into a predetermined volume to obtain a required glass melt lump, which is press molded in a press mold to produce a thin disk-shaped substrate blank. Next, a center hole is provided in the obtained substrate blank, and polishing processes such as inner and outer periphery processing and lapping and polishing are performed on both main surfaces. Next, a cleaning process including acid cleaning and alkali cleaning is performed to obtain a disk-shaped substrate. For the various processes performed to obtain the magnetic recording medium substrate, known technologies related to the manufacture of magnetic recording medium substrates can be applied. In the polishing process, the glass is usually polished by supplying an abrasive (slurry) between the glass to be polished and the polishing pad. However, if foreign matter (e.g., sludge-like foreign matter) formed by the reaction between glass components and abrasives adheres to and accumulates on the polishing pad, the polishing efficiency (polishing rate) in the polishing process decreases. Therefore, when the polishing pad can no longer achieve a predetermined polishing efficiency, it is normal to replace the polishing pad. From the viewpoint of productivity, the longer the same polishing pad can be used, the more productive it is.
[0061] In one embodiment, the magnetic recording medium substrate has a homogeneous surface and internal composition. Here, the homogeneous surface and internal composition means that ion exchange has not been performed (i.e., the substrate does not have an ion exchange layer). The magnetic recording medium substrate without an ion exchange layer is manufactured without ion exchange processing, and therefore the manufacturing cost can be significantly reduced.
[0062] In one embodiment, the magnetic recording medium substrate has an ion exchange layer on a part or the whole of the surface. Since the ion exchange layer exhibits compressive stress, the presence or absence of the ion exchange layer can be confirmed by breaking the substrate perpendicularly to the main surface and obtaining a stress profile on the fracture surface by the Babinet method. The "main surface" is the surface on which the magnetic recording layer of the substrate is provided or is provided. This surface is called the main surface because it is the surface with the largest area among the surfaces of the magnetic recording medium substrate, and in the case of a disk-shaped magnetic recording medium, it corresponds to the circular surface of the disk (excluding the central hole if there is one). The presence or absence of the ion exchange layer can also be confirmed by a method of measuring the concentration distribution of alkali metal ions in the depth direction from the substrate surface, etc.
[0063] The ion exchange layer can be formed by contacting an alkali salt with the substrate surface at high temperature and exchanging the alkali metal ions in the alkali salt with the alkali metal ions in the substrate. For ion exchange (also called "strengthening treatment" or "chemical strengthening"), known techniques can be applied, and for example, see paragraphs 0068 to 0069 of WO2011 / 019010A1.
[0064] The magnetic recording medium substrate has a thickness of, for example, 1.5 mm or less, preferably 1.2 mm or less, more preferably 1.0 mm or less, even more preferably 0.8 mm or less, even more preferably less than 0.8 mm, even more preferably 0.7 mm or less, and even more preferably 0.6 mm or less. The thickness of the magnetic recording medium substrate is, for example, 0.3 mm or more. It is preferable to be able to reduce the thickness of the magnetic recording medium substrate from the viewpoint of improving the recording capacity of HDDs. The magnetic recording medium substrate is preferably in the shape of a disk having a central hole.
[0065] The magnetic recording medium substrate can be made of amorphous glass, which can provide superior surface smoothness when processed into a substrate compared to crystallized glass.
[0066] The magnetic recording medium substrate is made of the glass for magnetic recording medium substrates according to one aspect of the present invention, and therefore can have the glass physical properties described above for the glass.
[0067] [Magnetic recording media] One aspect of the present invention relates to a magnetic recording medium having a magnetic recording layer on the above magnetic recording medium substrate.
[0068] Magnetic recording media are called magnetic disks, hard disks, etc., and are suitable for use in various magnetic recording and reproducing devices, such as internal storage devices (fixed disks, etc.) of desktop personal computers, server computers, notebook personal computers, mobile personal computers, etc., internal storage devices of portable recording and reproducing devices that record and replay images and / or sounds, recording and replay devices for car audio, etc. In the present invention and this specification, the term "magnetic recording and replay device" refers to a device that is capable of either or both of magnetically recording information and magnetically replaying information.
[0069] A magnetic recording medium has a configuration in which, for example, on the main surface of a magnetic recording medium substrate, at least an adhesive layer, an underlayer, a magnetic layer (magnetic recording layer), a protective layer, and a lubricant layer are laminated in that order from closest to the main surface. For example, the magnetic recording medium substrate is introduced into a film-forming apparatus that has been evacuated, and an adhesion layer to a magnetic layer are sequentially formed on the main surface of the magnetic recording medium substrate in an Ar atmosphere by DC (Direct Current) magnetron sputtering. For example, CrTi can be used as the adhesion layer, and for example, a material containing Ru or MgO can be used as the underlayer. In addition, a soft magnetic layer and a heat sink layer may be added as appropriate. After the above film formation, for example, a protective layer is formed using C2H4 by CVD (Chemical Vapor Deposition), and a nitriding process is performed in the same chamber to introduce nitrogen into the surface, thereby forming a magnetic recording medium. After that, for example, PFPE (polyfluoropolyether) can be applied to the protective layer by dip coating to form a lubricating layer.
[0070] For higher density recording of the magnetic recording medium, it is preferable that the magnetic recording layer contains a magnetic material with high magnetic anisotropy energy. From this point of view, a preferable magnetic material is an Fe-Pt magnetic material or a Co-Pt magnetic material. Here, "based" means containing. That is, the magnetic recording medium preferably has a magnetic recording layer containing Fe and Pt, or Co and Pt as the magnetic recording layer. For the magnetic recording layer containing such a magnetic material and the film formation method thereof, reference can be made to paragraph 0074 of WO2011 / 019010A1 and the description of the examples in the same publication. In addition, it is preferable that the magnetic recording medium having such a magnetic recording layer is applied to a magnetic recording device using a recording method called an energy-assisted recording method. Among the energy-assisted recording methods, a recording method in which magnetization reversal is assisted by irradiation of near-field light or the like is called a thermally assisted recording method, and a recording method in which magnetization reversal is assisted by microwaves is called a microwave-assisted recording method. For details of these, reference can be made to paragraph 0075 of WO2011 / 019010A1. As the magnetic material for forming the magnetic recording layer, a conventional CoPtCr-based material may be used.
[0071] In recent years, a DFH (Dynamic Flying Height) mechanism has been installed on a magnetic head to significantly narrow the gap between the read / write element of the magnetic head and the surface of the magnetic recording medium (reducing the flying height), thereby achieving even higher recording density. The DFH mechanism is a function of providing a heating unit such as a very small heater near the read / write element of the magnetic head and protruding only the periphery of the element toward the surface of the medium. This reduces the distance (flying height) between the magnetic head and the magnetic recording layer of the medium, making it possible to pick up signals from smaller magnetic particles and achieve even higher recording density. In one embodiment, the magnetic recording medium substrate can be used as a substrate for a magnetic recording medium applied to a magnetic recording and reproducing device equipped with a magnetic head equipped with a DFH mechanism.
[0072] There are no particular limitations on the dimensions of the magnetic recording medium substrate (e.g., glass substrate for magnetic disk) and the magnetic recording medium (e.g., magnetic disk), but for example, since high recording density is possible, it is also possible to miniaturize the medium and substrate. Also, in order to increase the recording capacity per magnetic recording medium, it is also possible to enlarge the medium and substrate. For example, the nominal diameter can of course be 2.5 inches, but it can also be smaller (e.g., 1 inch, 1.8 inches), or 3 inches, 3.5 inches, or even larger.
[0073] [Glass spacer for magnetic recording / reproducing devices] A glass spacer for a magnetic recording / reproducing device according to one embodiment of the present invention (hereinafter also referred to as “glass spacer a”) is made of glass A. Moreover, a glass spacer according to another embodiment of the present invention (hereinafter also referred to as “glass spacer b”) is made of glass B.
[0074] The magnetic recording medium can be used to magnetically record and / or reproduce information in a magnetic recording / reproducing device. The magnetic recording / reproducing device is usually provided with a spacer for fixing the magnetic recording medium to the spindle of a spindle motor and / or for maintaining a distance between a plurality of magnetic recording media. In recent years, it has been proposed to use a glass spacer as such a spacer. For reasons similar to those detailed above regarding the glass for the magnetic recording medium substrate, it is desired that the glass spacer also has excellent heat resistance and productivity. In contrast, the glass having the above composition can have excellent heat resistance and productivity, and is therefore suitable as a glass spacer for a magnetic recording / reproducing device.
[0075] The spacer for the magnetic recording and reproducing device is a ring-shaped member, and the details of the configuration, manufacturing method, etc. of the glass spacer are publicly known. In addition, for the manufacturing method of the glass spacer, the above description of the manufacturing method of glass for magnetic recording medium substrate and the manufacturing method of the magnetic recording medium substrate can be referred to. In addition, for other details such as the glass composition and glass physical properties of the glass spacer a, the above description of the glass A, the magnetic recording medium substrate made of glass A, and the magnetic recording medium having such a magnetic recording medium substrate can be referred to. In addition, for other details such as the glass composition and glass physical properties of the glass spacer b, the above description of the glass B, the magnetic recording medium substrate made of glass B, and the magnetic recording medium having such a magnetic recording medium substrate can be referred to. The spacer for the magnetic recording and reproducing device may be made of glass spacer a or glass spacer b, or may have one or more layers of a conductive film or the like on the surface of glass spacer a or glass spacer b. For example, in order to remove static electricity generated during rotation of the magnetic recording medium, a conductive film of NiP alloy or the like may be formed on the surface of the glass spacer by plating, immersion, deposition, sputtering, or the like. In addition, the glass spacer can be polished to increase the surface smoothness (for example, the average surface roughness Ra is 1 μm or less), which can strengthen the adhesion between the magnetic recording medium and the spacer and suppress the occurrence of positional deviation.
[0076] [Magnetic recording and playback device] One aspect of the present invention is Magnetic recording medium a, Magnetic recording medium b, Glass spacer a, and Glass spacer b, A magnetic recording and reproducing device including one or more selected from the group consisting of: Regarding.
[0077] A magnetic recording and reproducing device includes at least one magnetic recording medium and at least one spacer, and typically further includes a spindle motor for rotating the magnetic recording medium, and at least one magnetic head for recording and / or reproducing information on the magnetic recording medium. The magnetic recording and reproducing device according to an embodiment of the present invention may include a magnetic recording medium according to an embodiment of the present invention (magnetic recording medium a and / or magnetic recording medium b) as at least one magnetic recording medium, and may also include a plurality of magnetic recording media according to an embodiment of the present invention. The magnetic recording and reproducing device according to an embodiment of the present invention may include a glass spacer according to an embodiment of the present invention (glass spacer a and / or glass spacer b) as at least one spacer, and may also include a plurality of glass spacers according to an embodiment of the present invention. A small difference between the thermal expansion coefficient of the magnetic recording medium and the thermal expansion coefficient of the spacer is preferable from the viewpoint of suppressing the occurrence of phenomena that may occur due to the difference between the thermal expansion coefficients of the two, such as distortion of the magnetic recording medium and a decrease in stability during rotation due to misalignment of the magnetic recording medium. From this viewpoint, the magnetic recording and reproducing device according to an embodiment of the present invention preferably includes a magnetic recording medium according to an embodiment of the present invention as at least one magnetic recording medium, or as more magnetic recording media when multiple magnetic recording media are included, and includes a glass spacer according to an embodiment of the present invention as at least one spacer, or as more spacers when multiple spacers are included. Furthermore, for example, in a magnetic recording and reproducing device according to one aspect of the present invention, the glass constituting the magnetic recording medium substrate included in the magnetic recording medium and the glass constituting the glass spacer can have the same glass composition.
[0078] The magnetic recording and reproducing device according to an embodiment of the present invention may include at least one of the magnetic recording medium according to an embodiment of the present invention and the glass spacer according to an embodiment of the present invention, and other aspects may be applied to known techniques related to magnetic recording and reproducing devices. In one embodiment, an energy-assisted magnetic recording head having an energy source (e.g., a heat source such as a laser light source, microwaves, etc.) for assisting magnetization reversal (assisting writing of a magnetic signal), a recording element portion, and a reproducing element portion can be used as the magnetic head. Such an energy-assisted recording magnetic recording and reproducing device including an energy-assisted recording head is useful as a magnetic recording and reproducing device having high recording density and high reliability. In addition, when manufacturing a magnetic recording medium used in an energy-assisted recording magnetic recording and reproducing device including a heat-assisted recording method including a heat-assisted magnetic recording head having a laser light source or the like, a magnetic recording layer including a magnetic material with high magnetic anisotropic energy may be formed on a magnetic recording medium substrate. To form such a magnetic recording layer, a film is usually formed at a high temperature, or a heat treatment is performed at a high temperature after the film is formed. As a magnetic recording medium substrate that can have high heat resistance to such high temperature treatment, the magnetic recording medium substrate according to an embodiment of the present invention is preferable. However, the magnetic recording and reproducing device according to one aspect of the present invention is not limited to the energy-assisted magnetic recording and reproducing device. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.
[0080] [Examples No. 1 to No. 71] Raw materials such as oxides, carbonates, nitrates, sulfates, and hydroxides were weighed and mixed to prepare blended raw materials so as to obtain glass having the composition shown in the following Tables 1 to 4. The blended raw materials were charged into a melting vat and heated and melted in the range of 1400 to 1600°C. The obtained molten glass was held in a fining vat at 1400 to 1550°C for 6 hours, and then the temperature was lowered (cooled down) and held in the range of 1200 to 1400°C for 1 hour, after which the molten glass was formed to obtain glasses (amorphous oxide glasses) for the following evaluations.
[0081] <Evaluation of glass properties> (1) Glass transition temperature (Tg), average linear expansion coefficient (α) The glass transition temperature Tg and the average linear expansion coefficient α at 100 to 300° C. of each glass were measured using a thermomechanical analysis (TMA) device.
[0082] (2) Young’s modulus The Young's modulus of each glass was measured by an ultrasonic method.
[0083] (3) Specific gravity The specific gravity of each glass was measured by Archimedes' method.
[0084] (4) Specific elastic modulus The specific elastic modulus was calculated from the Young's modulus obtained in (2) above and the specific gravity obtained in (3).
[0085] (5) Glass stability 100g of each glass was placed in a platinum crucible, and each crucible was placed in a heating furnace with the furnace temperature set to 1250°C, 1270°C, or 1300°C, and left for 16 hours (retention test) while maintaining the furnace temperature. After 16 hours, the crucible was removed from the heating furnace, and the glass in the crucible was transferred onto a refractory material and cooled to room temperature. The presence or absence of crystals in each glass was observed with an optical microscope (magnification 40 to 100 times) and evaluated according to the following criteria. A: No crystals on the glass surface, inside, or at the interface with the platinum crucible bottom B: There are less than 10 crystals with a diameter of several tens of μm on the glass surface and on the interface with the bottom of the platinum crucible per 100 g. C: More than 10 crystals with a diameter of several tens of μm on the glass surface and on the interface with the bottom of the platinum crucible per 100 g D: Crystals inside the glass E: Crystals are present on the glass surface, inside, and at the interface with the platinum crucible bottom.
[0086] <Preparation of magnetic recording medium substrate> (1) Preparation of substrate blank Next, a disk-shaped substrate blank was produced by the following method A or B. Moreover, a glass blank for producing a glass spacer for a magnetic recording / reproducing device can be obtained by the same method. (Method A) For glass having the composition shown in the table below, clarified and homogenized molten glass was flowed out of the flow pipe at a constant flow rate and received by a lower mold for press molding, and the flowed molten glass was cut with a cutting blade so that a predetermined amount of molten glass gob was obtained on the lower mold. The lower mold with the molten glass gob placed thereon was immediately removed from the bottom of the pipe, and the molten glass was press-molded into a thin disk shape with a diameter of 99 mm and a thickness of 0.7 mm using an upper mold and a body mold opposed to the lower mold. The press-molded product was cooled to a temperature at which it would not deform, and then removed from the mold and annealed to obtain a substrate blank. In the above molding, the flowing molten glass was successively molded into disk-shaped substrate blanks using multiple lower molds. (Method B) For glass having the composition shown in the table below, clarified and homogenized molten glass was continuously poured from above into a heat-resistant mold having a cylindrical through-hole, formed into a cylindrical shape, and removed from the bottom of the through-hole. After annealing the removed glass, the glass was sliced at regular intervals in a direction perpendicular to the cylindrical axis using a multi-wire saw to produce disk-shaped substrate blanks. Although the above-mentioned methods A and B were adopted in this embodiment, the following methods C and D are also suitable as methods for manufacturing a disk-shaped substrate blank. The following methods C and D are also suitable as methods for manufacturing a glass blank for producing a glass spacer for a magnetic recording / reproducing device. (Method C) Molten glass can be poured onto a float bath and formed into a sheet of glass (forming by the float method), and then annealed, after which a disk of glass can be hollowed out from the sheet of glass to obtain a substrate blank. (Method D) Molten glass can also be formed into a sheet of glass by the overflow downdraw method (fusion method), annealed, and then a disk of glass can be hollowed out from the sheet of glass to obtain a substrate blank.
[0087] (2) Preparation of glass substrate A through hole was drilled in the center of the substrate blank obtained by each of the above methods, the outer and inner circumferences were ground, and the main surfaces of the disks were lapped and polished (mirror polished) to finish them into glass substrates for magnetic disks with a diameter of 97 mm and a thickness of 0.5 mm. Also, by using the same method, glass blanks for producing glass spacers for magnetic recording and reproducing devices can be finished into glass spacers for magnetic recording and reproducing devices. The glass substrate obtained above was washed with a 1.7% by mass aqueous solution of hydrofluoric acid (H2SiF) and then with a 1% by mass aqueous solution of potassium hydroxide, and then rinsed with pure water and dried. When the surface of the substrate made from the glass of the example was observed under magnification, no surface roughness was observed, and the surface was smooth. For each glass composition, four or more glass substrates were prepared and used for the following evaluation (1), (2), or (3) or for preparing a magnetic recording medium as described below.
[0088] <Productivity evaluation> (1) Evaluation of solubility (1500℃ solubility) Raw materials such as oxides, carbonates, nitrates, sulfates, and hydroxides were weighed and mixed to obtain glass with the composition shown in Table 1 below. This raw material mixture was charged into a melting tank and stirred several times while being heated at 1500°C. The molten material in the melting tank was then observed under a microscope under magnification to check for residual raw materials. Cases with no residual raw materials were rated as "A," and cases with residual raw materials were rated as "B."
[0089] (2) Total amount of glass polished before polishing pad replacement A through hole was drilled in the center of the substrate blank obtained by the method described above, and the outer and inner circumferences were ground, and the main surface of the disk was lapped, and then polished (mirror polished) using a commercially available abrasive and polishing pad. The unused polishing pad was used until the polishing efficiency (polishing rate) normally acceptable in actual production could not be maintained (i.e., until replacement was required). The amount of glass (thickness) polished until replacement was required was calculated as "total amount of glass polished until replacement of the polishing pad" by (thickness before polishing - thickness after polishing) x number of polished sheets. The larger the calculated total amount of glass, the longer the same polishing pad can be used in the polishing process, which is preferable from the viewpoint of productivity. The total amount of glass polished until replacement of the polishing pad is preferably 300 μm or more, more preferably 500 μm or more, and even more preferably 700 μm or more.
[0090] The above results are shown in Tables 1 to 4 (Tables 1-1 to 4-3).
[0091] [Table 1-1]
[0092] [Table 1-2]
[0093] [Table 1-3]
[0094] [Table 2-1]
[0095] [Table 2-2]
[0096] [Table 2-3]
[0097] [Table 3-1]
[0098] [Table 3-2]
[0099] [Table 3-3]
[0100] [Table 4-1]
[0101] [Table 4-2]
[0102] [Table 4-3]
[0103] [Magnetic recording medium (magnetic disk) production] By the following method, an adhesive layer, an underlayer, a magnetic recording layer, a protective layer, and a lubricant layer were formed in this order on the main surface of the magnetic disk glass substrate prepared above, to obtain a magnetic disk.
[0104] First, using a deposition apparatus that had been evacuated, an adhesive layer, an underlayer, and a magnetic recording layer were successively deposited in an Ar atmosphere by DC magnetron sputtering.
[0105] At this time, the adhesion layer was formed using a CrTi target so as to be an amorphous CrTi layer with a thickness of 20 nm. Then, a 10 nm thick layer made of MgO was formed as an underlayer. The magnetic recording layer was formed at a deposition temperature of 200 to 400°C using an FePtC or CoPtC target so as to be a 10 nm thick granular layer of FePt or CoPt.
[0106] The magnetic disk, which had been deposited up to the magnetic recording layer, was transferred from the deposition device to a heating furnace and annealed. The temperature in the heating furnace during annealing was in the range of 500 to 700°C. This annealing process 10 Magnetic particles of CoPt-based alloy or FePt-based alloy with an ordered structure are formed. 10 Heating may be applied so as to produce an ordered structure.
[0107] Next, a protective layer made of hydrogenated carbon was formed to a thickness of 3 nm by CVD using ethylene as the material gas. After this, a lubricating layer made of PFPE (perfluoropolyether) was formed by dip coating. The lubricating layer had a thickness of 1 nm. A magnetic disk was obtained through the above manufacturing process. The obtained magnetic disk was mounted in a hard disk drive equipped with a DFH mechanism, and magnetic signals were recorded and reproduced in the recording area on the main surface of the magnetic disk at a recording density of 1000 gigabits per square inch. No collision between the magnetic head and the magnetic disk surface (crash failure) was observed.
[0108] In addition, a glass spacer obtained by the above manufacturing process using the glass of the embodiment and having a conductive NiP alloy film formed on its surface (glass spacer with NiP alloy film) was mounted in a hard disk drive equipped with a DFH mechanism, and magnetic signals were recorded and reproduced at a recording density of 1,000 gigabits per square inch in a recording area on the main surface of a magnetic disk separately prepared using a substrate made of a material different from the glass of one embodiment of the present invention.No collision between the magnetic head and the magnetic disk surface (crash failure) was observed.
[0109] Furthermore, when the magnetic disk and the glass spacer with NiP alloy film manufactured above using the same glass material according to one embodiment of the present invention were mounted on a hard disk drive equipped with a DFH mechanism, and magnetic signals were recorded and reproduced in the recording area on the main surface of the magnetic disk at a recording density of 1000 gigabits per square inch, no phenomenon (crash failure) was observed in which the magnetic head collided with the magnetic disk surface. Here, since the glass substrate and the glass spacer included in the magnetic disk are made of the same glass material, the phenomenon that may occur due to the difference in thermal expansion coefficient described above does not occur.
[0110] According to one aspect of the present invention, it is possible to provide a magnetic recording medium suitable for high density recording.
[0111] [Comparative Example] For the glass compositions of the examples shown in Table 5 below, which are described in Patent Document 1 (JP 2015-224150 A), productivity was evaluated in the same manner as in the above examples. The results are shown in Table 5.
[0112] [Table 5]
[0113] Finally, the above-mentioned aspects will be summarized.
[0114] According to one embodiment, there is provided a glass (Glass A) for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device, in which the total content of Li2O, Na2O, K2O, B2O3 and ZnO (Li2O+Na2O+K2O+B2O3+ZnO) is from 0 mol% to 3 mol%, the molar ratio of the total content of Al2O3 and MgO to the total content of SiO2 and CaO [(Al2O3+MgO) / (SiO2+CaO)] is from 0.30 to 0.6, the total content of SiO2 and Al2O3 (SiO2+Al2O3) is from 64 mol% to 85 mol%, and the total content of SiO2, Al2O3, MgO and CaO (SiO2+Al2O3+MgO+CaO) is from 87 mol% to 98 mol%.
[0115] According to one embodiment, there is provided a glass (Glass B) for a magnetic recording medium substrate or a glass spacer for a magnetic recording and reproducing device, in which the molar ratio of the total content of Al2O3 and MgO to the total content of SiO2 and CaO [(Al2O3+MgO) / (SiO2+CaO)] is from 0.30 to 0.6, the total content of SiO2 and Al2O3 (SiO2+Al2O3) is from 64 mol% to 85 mol%, the total content of SiO2, Al2O3, MgO and CaO (SiO2+Al2O3+MgO+CaO) is from 87 mol% to 98 mol%, and the glass transition temperature is 740°C or higher.
[0116] Glass A and Glass B can be glasses for use in magnetic recording medium substrates or glass spacers for magnetic recording / reproducing devices, which are excellent in both heat resistance and productivity.
[0117] In one embodiment, in glass A and glass B, the SiO2 content can be 55 mol % or more and 66 mol % or less.
[0118] In one embodiment, in glass A and glass B, the Al2O3 content can be 10 mol % or more and 18 mol % or less.
[0119] In one embodiment, in glass A and glass B, the MgO content can be 8 mol % or more and 20 mol % or less.
[0120] In one embodiment, in glass A and glass B, the CaO content can be 0 mol % or more and 7 mol % or less.
[0121] In one embodiment, in glass A and glass B, the molar ratio of the CaO content to the total content of MgO, CaO, SrO, and BaO [CaO / (MgO+CaO+SrO+BaO)] can be 0.4 or less.
[0122] In one embodiment, the Young's modulus of glass A and glass B can be 86 GPa or greater.
[0123] In one embodiment, the specific gravity of glass A and glass B can be 2.8 or less.
[0124] In one embodiment, the specific elastic modulus of glass A and glass B can be 30 MNm / kg or greater.
[0125] According to one embodiment, a magnetic recording medium substrate (magnetic recording medium substrate a) made of glass A is provided.
[0126] According to one embodiment, a magnetic recording medium substrate (magnetic recording medium substrate b) made of Glass B is provided.
[0127] According to one embodiment, there is provided a magnetic recording medium having the above magnetic recording medium substrate and a magnetic recording layer.
[0128] According to one embodiment, there is provided a glass spacer for a magnetic recording / reproducing device made of glass A (glass spacer a).
[0129] According to one embodiment, there is provided a glass spacer (glass spacer b) for a magnetic recording / reproducing device made of glass B.
[0130] According to one embodiment, there is provided a magnetic recording and reproducing device including one or more selected from the group consisting of a magnetic recording medium a, a magnetic recording medium b, a glass spacer a, and a glass spacer b.
[0131] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by adjusting the composition as described in the specification to the glass compositions exemplified above, it is possible to produce a glass for a magnetic recording medium substrate and a glass spacer for a magnetic recording / reproducing device according to one embodiment of the present invention. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.
Claims
1. SiO 2 and CaO content 2 O 3 The molar ratio of the total content of Al and MgO [(Al 2 O 3 +MgO) / (SiO 2 + CaO)] is 0.451 or more and 0.6 or less, SiO 2 and Al 2 O 3 The total content of 2 +Al 2 O 3 ) is 64 mol % or more and 85 mol % or less, SiO 2 , Al 2 O 3 , the total content of MgO and CaO (SiO 2 +Al 2 O 3 + MgO + CaO) is 87 mol % or more and 98 mol % or less, TiO 2 and ZrO 2 The total content of TiO 2 + ZrO 2 ) is 0.5 mol % or more, A 2 O 3 The content is 10 mol% or more and 18 mol% or less, The CaO content is 0 mol% or more and 7 mol% or less, Li 2 O and Na 2 does not contain one or both of O; and The average linear expansion coefficient α at 100 to 300°C is 68 x 10 -7 / °C or less for use as a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device.
2. SiO 2 and CaO content 2 O 3 The molar ratio of the total content of Al and MgO [(Al 2 O 3 +MgO) / (SiO 2 + CaO)] is 0.417 or more and 0.6 or less, SiO 2 and Al 2 O 3 The total content of 2 +Al 2 O 3 ) is 64 mol % or more and 85 mol % or less, SiO 2 , Al 2 O 3 , the total content of MgO and CaO (SiO 2 +Al 2 O 3 + MgO + CaO) is 87 mol % or more and 98 mol % or less, TiO 2 and ZrO 2 The total content of TiO 2 + ZrO 2 ) is 0.5 mol % or more, B 2 O 3 The content is 0 mol% or more and 1 mol% or less, A 2 O 3 The content is 10 mol% or more and 18 mol% or less, The CaO content is 0 mol% or more and 7 mol% or less, Li 2 O and Na 2 does not contain one or both of O; and The average linear expansion coefficient α at 100 to 300°C is 68 x 10 -7 / °C or less for use as a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device.
3. SiO 2 and CaO content 2 O 3 The molar ratio of the total content of Al and MgO [(Al 2 O 3 +MgO) / (SiO 2 + CaO)] is 0.451 or more and 0.6 or less, SiO 2 and Al 2 O 3 The total content of 2 +Al 2 O 3 ) is 64 mol % or more and 85 mol % or less, SiO 2 , Al 2 O 3 , the total content of MgO and CaO (SiO 2 +Al 2 O 3 + MgO + CaO) is 87 mol % or more and 98 mol % or less, TiO 2 and ZrO 2 The total content of TiO 2 + ZrO 2 ) is 0.5 mol % or more, A 2 O 3 The content is 10 mol% or more and 18 mol% or less, The CaO content is 0 mol% or more and 7 mol% or less, A glass transition temperature of 740° C. or higher, and The average linear expansion coefficient α at 100 to 300°C is 68 x 10 -7 / °C or less for use as a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device.
4. SiO 2 and CaO content 2 O 3 The molar ratio of the total content of Al and MgO [(Al 2 O 3 +MgO) / (SiO 2 + CaO)] is 0.417 or more and 0.6 or less, SiO 2 and Al 2 O 3 The total content of 2 +Al 2 O 3 ) is 64 mol % or more and 85 mol % or less, SiO 2 , Al 2 O 3 , the total content of MgO and CaO (SiO 2 +Al 2 O 3 + MgO + CaO) is 87 mol % or more and 98 mol % or less, TiO 2 and ZrO 2 The total content of TiO 2 + ZrO 2 ) is 0.5 mol % or more, B 2 O 3 The content is 0 mol% or more and 1 mol% or less, A 2 O 3 The content is 10 mol% or more and 18 mol% or less, The CaO content is 0 mol% or more and 7 mol% or less, A glass transition temperature of 740° C. or higher, and The average linear expansion coefficient α at 100 to 300°C is 68 x 10 -7 / °C or less for use as a magnetic recording medium substrate or a glass spacer for a magnetic recording / reproducing device.
5. SiO 2 The glass according to any one of claims 1 to 4, wherein the content is from 55 mol% to 66 mol%.
6. 6. The glass according to claim 1, wherein the MgO content is from 8 mol % to 20 mol %.
7. 7. The glass according to claim 1, wherein a molar ratio of the content of CaO to the total content of MgO, CaO, SrO and BaO, [CaO / (MgO+CaO+SrO+BaO)], is 0.4 or less.
8. 8. The glass according to claim 1, having a Young's modulus of 86 GPa or more.
9. 9. The glass according to claim 1, having a specific gravity of 2.8 or less.
10. 10. The glass according to claim 1, having a specific elastic modulus of at least 30 MNm / kg.
11. A magnetic recording medium substrate made of the glass according to any one of claims 1 to 10.
12. A magnetic recording medium comprising the magnetic recording medium substrate according to claim 11 and a magnetic recording layer.
13. A glass spacer for a magnetic recording / reproducing device, comprising the glass according to any one of claims 1 to 10.
14. The magnetic recording medium according to claim 12, The glass spacer for a magnetic recording / reproducing device according to claim 13 . A magnetic recording and reproducing device comprising one or more selected from the group consisting of:
Citation Information
Patent Citations
High rigidity glass ceramic substrate for information magnetic storage medium
JP2000187828A
Glass for magnetic recording medium substrate and magnetic recording medium substrate
JP2015054794A
Method for producing alkali-free glass
JP2015224150A
Method for producing magnetic disk and glass substrate for information recording media
WO2013183569A1
Alkali-free glass and method for producing same
WO2013183626A1